2021
DOI: 10.1515/hf-2021-0169
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the biotic degradation hazard of wood in Europe – biophysical background, engineering applications, and climate change-induced prospects

Abstract: Construction using timber has seen a resurgence in light of global climate mitigation policies. Wood is a renewable resource, and engineered wood products are proving to be competitive against concrete and steel while having several advantages. However, while the renewable nature of wood in construction is a beneficial property for climate mitigation policies, the process of biodegradation introduces a challenge for service life planning. A review of hazard mapping is presented while developing contemporary ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
2
5
0
Order By: Relevance
“…The Scheffer Climate Index of this site is 42.1 [57], which indicates intermediately favorable conditions for decay. This index is similar to other reports regarding the SCI of different countries, including Hungary [63][64][65][66].…”
Section: Weather Exposuresupporting
confidence: 90%
“…The Scheffer Climate Index of this site is 42.1 [57], which indicates intermediately favorable conditions for decay. This index is similar to other reports regarding the SCI of different countries, including Hungary [63][64][65][66].…”
Section: Weather Exposuresupporting
confidence: 90%
“…During the interviews, it was reported that the termite spread will increase due to climate change, especially in wood products exported to hot countries, and that necessary measures should be taken accordingly. This finding can be associated with the finding underlined in the study by van Niekerk et al [103] that those warmer climates are expected to increase the metabolic activities of all wood-threatening organisms such as termites, leading to an overall reduction in the service life of wooden structures.…”
Section: Discussionsupporting
confidence: 65%
“…A majority of future buildings will be erected in hot and humid climates, favorable conditions not only for the growth of decay fungi but also for termites, which are major threats to wood structures. Research on efficient but environmentally friendly protection against termites is of utmost importance, also given the fact that climate change will favor the spreading of termites around the globe …”
Section: Carbon Impact and Recyclability Of Engineered Wood Productsmentioning
confidence: 99%